Clinical Profile of Patients with Chronic Kidney Disease (Academia Journal of Medicine, 2020)
Background: DM is the leading cause of end-stage renal disease (ESRD), non-traumatic lower extremity amputations, and adult blindness. It  also predisposes to cardiovascular diseases. With an increasing incidence worldwide, DM will be likely a leading cause of morbidity and  mortality in the future29. Chronic kidney disease (CKD) encompasses a spectrum of different pathophysiologic processes associated with  abnormal kidney function and a progressive decline in glomerular filtration rate. Subjects and Methods: A written informed consent was  obtained from all patients. History regarding the duration of hypertension, the medications being taken, coexisting medical problems, and  symptomatology suggestive of ischemic heart disease, transient ischemic attacks and that of renal involvement were documented. A detailed  history, anthropometry, vital signs, clinical examination and laboratory parameters were recorded for both the study group. Results: The Study  reveals that, there was statistically very highly significant difference of age among Type 2 diabetes mellitus with CKD and Non-diabetic  patients with CKD (P0.05).It’s found that vegetarians have less SUA level when compare to mixed diet patients.
Keywords: Chronic kidney disease; DM; GFR